Psychosocial Predictors of Academic Stress Among High-Achieving Students: Prediktor Psikososial Stres Akademik di Kalangan Siswa Berprestasi Tinggi - Adinda Rizky Oktavia; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic stress represents a significant psychological challenge among adolescents facing increasing educational demands and performance expectations. Specific Background: Psychosocial resources such as social support, resilience, and self-esteem are considered important internal and external factors associated with students’ ability to manage academic pressure, particularly among high-achieving students who encounter intensified academic and performance demands. Knowledge Gap: Although previous studies have examined these variables separately, limited research has analyzed their combined relationships and mediating mechanisms within a single empirical model focusing on high-achieving students. Aims: This study aimed to examine the relationships between social support, resilience, self-esteem, and academic stress, and to analyze the mediating role of self-esteem among high-achieving students. Results: Using a quantitative correlational design with 200 students and multiple regression analysis, findings revealed significant negative relationships between social support, resilience, and self-esteem with academic stress. Self-esteem demonstrated the strongest correlation with academic stress, while social support showed the lowest correlation. The regression model explained 43.1% of the variance in academic stress, indicating that higher levels of psychosocial resources were associated with lower stress levels. Novelty: This study integrates social support, resilience, and self-esteem within a single analytical framework and empirically confirms the mediating role of self-esteem in explaining academic stress among high-achieving students. Implications: The findings suggest that strengthening psychosocial resources, particularly self-esteem alongside supportive environments and resilience development, may contribute to healthier learning conditions and improved student psychological well-being. Highlights: Psychological Resources Jointly Accounted for 43.1% Variance in Student Pressure Levels. Confidence-Related Factors Showed the Strongest Statistical Association With Reduced Strain. Combined Psychosocial Variables Demonstrated Significant Simultaneous Relationships With Learner Tension. Keywords: Academic Stres, Social Support, Resilience, Self-Esteem, High-Achieving Students